2021
DOI: 10.7717/peerj.11695
|View full text |Cite
|
Sign up to set email alerts
|

Depression and low physical activity are related to sarcopenia in hemodialysis: a single-center study

Abstract: Background The number of patients who suffer from chronic renal failure (CRF) has widely increased worldwide. Patients with advanced stages of CRF experience a gradual and progressive loss of muscle and fat mass leading to decreased physical activity and mental health problems. The loss of muscle mass in CRF might contribute to the development of sarcopenia. Therefore, this study aimed to explore the prevalence of sarcopenia and to determine the relationship of physical activity and mental state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…The studies were published between 2014 and 2022 and varied in sample size (33 to 645 patients). Among the included studies, twenty-one studies were conducted in Asian countries (China, Iran, Japan, Korea, Taiwan, Thailand, and Turkey) [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], nine in European countries (France, Sweden, Spain, and United Kingdom) [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], eight in South American countries (Brazil and Argentina) [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ], two in the USA [ 57 , 58 ], and the remaining one in Australia [ 59 ]. These studies yielded a total sample of five continents (Asia: 45.6%, Europe: 25.9%, North America: 14.3%, South America: 13.7%, and Australia: 0.5%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies were published between 2014 and 2022 and varied in sample size (33 to 645 patients). Among the included studies, twenty-one studies were conducted in Asian countries (China, Iran, Japan, Korea, Taiwan, Thailand, and Turkey) [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], nine in European countries (France, Sweden, Spain, and United Kingdom) [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], eight in South American countries (Brazil and Argentina) [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ], two in the USA [ 57 , 58 ], and the remaining one in Australia [ 59 ]. These studies yielded a total sample of five continents (Asia: 45.6%, Europe: 25.9%, North America: 14.3%, South America: 13.7%, and Australia: 0.5%).…”
Section: Resultsmentioning
confidence: 99%
“…These studies yielded a total sample of five continents (Asia: 45.6%, Europe: 25.9%, North America: 14.3%, South America: 13.7%, and Australia: 0.5%). Thirty-one studies [ 19 , 22 , 23 , 24 , 25 , 26 , 27 , 29 , 30 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 43 , 44 , 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ] were conducted in HD population, seven studies [ 20 , 21 , 28 , 31 , 32 , 42 , 47 ] were performed in PD population, and three studies [ 24 , 33 , 59 ] were carried out in mixed populations (both HD and PD). Of the included patients, the mean age was 62.3 years, 61.4% were male, and 38.6% had diabetes mellitus as a comorbidity with a mean dialysis vintage of 52.4 months.…”
Section: Resultsmentioning
confidence: 99%
“…Patients on hemodialysis have a higher risk of depression when their capacity to engage in physical activity is reduced [ 5 ]. This may be related to physical burdens, quality of life, and role loss of such patients because of their chronic disease [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Common comorbidities include hypertension, diabetes, and cardiovascular diseases [ 3 ]. When a patient’s comorbidity index score increases during their hemodialysis treatment, they are more likely to experience reduced physical function and activity, increased negative emotions, and increased disease severity [ 4 , 5 ]. Patients on hemodialysis with a greater number of comorbidities have been reported to have more severe depression, higher levels of anxiety [ 6 ], and higher fatigue scores [ 7 ] than those with fewer comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies, which explored sarcopenia and depression indicated that individuals with sarcopenia had a high depression score or depressive symptoms. 22,[31][32][33] In the present study, it should be noted that low response rate to the PHQ-9 items in HF was observed (2.13AE3.14 scores), which may have limited the ability to determine the increased risk for scoring high on sarcopenia.…”
Section: P-value P-valuementioning
confidence: 56%